Understanding and Managing Risks Caused by Covid 19 Pandemic - Cvetkovski, Sergej; Pavleski, Aleksandar; Spasov, Nikolco (University “St. Kliment Ohridski”- Bitola Faculty of Security- Skopje, 2021)
The rapidly growing and dynamic global developments of COVID-19 are creating unprecedented levels of uncertainty on a personal, national, regional and global level. Human security and the protection of life have become the most important priority at all these levels. In this regard, governments need to understand the way different threats and risks intersect. Actually, we all respond to risks and policies in different ways, and we all have different preferences and make different choices. Understanding these issues is crucial to effectively managing this COVID-19 pandemic emergency. Still, the dilemma of the government’s priority for overall security and its effects should be noted. A complete COVID-19 lockdown will save lives, but it will also have severe consequences, and some will lose their livelihoods completely. In addition, it is difficult to understand something like a pandemic that happens very rarely, and when it does, it is different from those that have happened before. This makes the management of COVID-19 much harder, especially in relation to how the states and other actors should respond. What prevention and treatment methods, including controls, should be implemented? This paper analyzes the characteristics of the risks and threats caused by the COVID-19 pandemic, as well as the challenges to successfully deal with them. The purpose of the analysis is to detect the most serious risks and threats, especially from a security aspect, and to determine the most acceptable methods and instruments for their management as well.
Keywords: COVID-19, pandemic, security, risks, management.